The convergence of race, ethnicity, and gender : multiple identities in counseling - Robinson, Tracy L (Sage, 2017)
It wasn't bad for a textbook . . . but it wasn't great either. Lots of good, solid statistics. Nice illustrative case studies. But the writing was dry at best, boring at worst. I usually ended up flipping through pages, errantly skimming, and after awhile didn't even bother to read the assigned chapters. I already knew the material, so I could afford to be negligent. My recommendation to teachers? It's not a bad book, especially for students new to the field of multicultural awareness, but if you can find another textbook with better writing and similar information, don't pick this one (unless students have to pay exorbitant prices).